Tales of Three Worlds - Archaeology and Beyond A Tribute to Sandro Salvatori. - Usai, Donatella (Archaeopress, 2020)
This book presents a series of papers in honour of Sandro Salvatori divided into three main sections reflecting his long years of work in Middle Asia, his time in Italy as an officer of the Archaeological Superintendency (Ministry of Cultural Heritage), and finally his studies on the prehistory of north-eastern Africa.